VD_FINDINFO 3/2011/PHC vom 11. Januar 2011 - VD Tribunal cantonal (2011)
DÉCISION INCIDENTE, SUSPENSION DE LA PROCÉDURE, PROCÉDURE PÉNALE | 53 CO, 1 al. 3 CPC, 123 CPC, 124 CPC, 147 CPC, 149 al. 4 CPC, 150 al. 2 CPC, 19 CPC, 92 al. 1 CPC, 174 TFJC, 4 TFJC